Capacitance Spectroscopy: A Versatile Approach To Resolving the Redox Density of States and Kinetics in Redox-Active Self-Assembled Monolayers - Bueno, Paulo Roberto [UNESP]; Mizzon, Giulia; Davis, Jason J. (Amer Chemical Soc, 2012)
Redox active self-assembled monolayers inherently possess both electrochemically addressable and polarizable components. The latter will contribute, with additional parasitic terms, to the iR drop effects within any form of electronic analysis, potentially distorting results. A capacitive analysis of such interfaces (Electroactive Mono layer Capacitance Spectroscopy), presented here, enables a clean mapping of both the thermodynamic and kinetic faradaic characteristics in a single experimental run, with parasitic nonfaradaic contributions (polarization and resistance terms) both spectrally resolved and cleanly removed. The methodology enables a rapid and undistorted quantification of accessible redox site density of states (reported directly by redox capacitance), molecular surface coverage, electron transfer kinetics, and reorganization energies with comparatively little experimental effort. Exemplified here with electroactive copper protein and ferrocene films the approach is equally applicable to any redox active interface.